Effect of the black sigatoka resistance gene bs1 and ploidy level in fruit and bunch traits of plantain banana hybrids - Craenen, K.; Ortíz, R. (1995)
Plantain (Musa spp., AAB group) cultivation is threatened by black sigatoka, an airborne fungal (Mycosphaerella fijiensis Morelet) leaf spot disease. Several traits in plantains and bananas are mainly affected by major genes. The host resistance response to black sigatoka is under the control of at least three different genes, one major recessive gene bs1 and two other independent additive alleles. Diploid and tetraploid plantain hybrids were evaluated for bunch weight, fruit weight, fruit length and fruit circumference. The F1 euploid hybrids were derived from interspecific crosses between the resistant diploid wild banana 'Calcutta 4' and the susceptible triploid plantain cultivars 'Obino l'Ewai' and 'Bobby Tannap'. Linear and multiple regression models, coefficients of determination, and Durbin-Watson statistics were used to determine the single and combined effects of the major locus for black sigatoka resistance and ploidy on the different traits in the progenies. Differences in yield were mainly due to changes in weight and girth of fruit, which are affected by black sigatoka disease. The combined effect of ploidy and resistance to black sigatoka was partially responsible for the quantitative trait variation in yield. As a result of the gene interaction in the black sigatoka resistance locus bs1, the partially resistant and less susceptible phenotypes showed higher yield than their more susceptible full sibs.